PROBLEMS IN THE IMPLEMENTATION OF ISLAMIC LAW IN THE CONTEMPORARY ERA - Meirison Meirison; Darni Yusna (UIN Imam Bonjol Padang, 2022)
One of the biggest obstacles to applying Islam as a social system in the modern secular state is the dilemma of codifying the provisions of Islamic Sharia within the mold of the Western legal system. Methods of preparing and promulgating those laws. Islamic Sharia, in its essence, is spiritual and devotional, and its material legislation tends to organize society so that it is possible to establish the orders of religion, achieve its purposes for people, and reform their conditions in this world and the Hereafter. Therefore, Sharia does not know boundaries, geographical boundaries, and the boundaries between this world and the Hereafter. And because the purposes of Western legislation are, in essence, purely materialistic, it seeks to achieve immediate material benefit to society. It does not concern itself with the condition of people in the Hereafter. The invocation of the concept of the Hereafter is a limit. The same when discussing Western legislation may cause ridicule and belittling among its supporters; Therefore, the hegemony of Western legislation with its vocabulary over Islam would result in a significant dilemma. The imams who are followed and accepted by a group of people, or the scholars whom others trust and obey, are human beings who make mistakes and are right. Their rulings are necessarily and inevitably affected by the level of knowledge, intelligence, integrity, whim, error, ignorance, and bias. When applying these rulings, they naturally need authority compelling political and capable of executing and implementing the provisions. And this authority is gained power by predominance and control, or the people elect it. Thus, whoever decides legitimacy is either a dominant political-military authority or an elected politician protected by a social contract upon which all or most of the citizens agree!